2011
DOI: 10.1001/archsurg.2010.311
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Trauma Center Use for Elderly Patients With Trauma

Abstract: Objectives To estimate the likelihood of trauma center admission for injured elderly patients with trauma, determine trends in trauma center admissions, and identify factors associated with trauma center use for elderly patients with trauma. Design Retrospective analysis. Setting Acute care hospitals in California. Patients All patients hospitalized for acute traumatic injuries during the period from January 1, 1999, to December 31, 2008 (n=430 081). Patients who had scheduled admissions for nonacute or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
55
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 60 publications
5
55
1
1
Order By: Relevance
“…However, injury severity and patient complexity was similar. Consistent with other studies, 18,38,43, 45 we found that these additional factors were indicative of the location of initial treatment as well as the likelihood of subsequent transfer. compared with children and adults younger than 55 years.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, injury severity and patient complexity was similar. Consistent with other studies, 18,38,43, 45 we found that these additional factors were indicative of the location of initial treatment as well as the likelihood of subsequent transfer. compared with children and adults younger than 55 years.…”
Section: Discussionsupporting
confidence: 91%
“…[9][10][11] This confluence of factors has resulted in identified patterns of undertriage associated with poorer outcomes 9,12-15 such as higher rates of trauma-related morbidity and mortality among older patients. [16][17][18] Possible causes for these age-related triage disparities include patient-level variables such as payer status, 19 differences in initial presentation, 2,19,20 location of injury, 21 type of injury, 22 and geographic distance from the nearest emergency department (ED). 23,24 In 1986, the American College of Surgeons (ACS) published the first Field Decision Scheme, which was updated in 1990, 1993, and 1999.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Males significantly more likely to be transported 131 or admitted 132 to a trauma center than females. Male trauma patients more often given priority 1, transported straight to trauma center, and allocated highest level of prehospital competence than females.…”
mentioning
confidence: 99%